Pengaruh Efikasi Diri, Kecerdasan Emosional, dan Motivasi Belajar Terhadap Prestasi Belajar Matematika Siswa SMA Kelas XI IPA - Aswin; Djadir; Rusli (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This study was conducted to determine effect of self efficacy, emotional intelegence, and learning motivation on Student’s mathematics Learning achievement of grade XI IPA of SMA at Makassar. This research is ex post facto research which is causality with research sample counted 132 students from class XI IPA SMA at Makassar selected by using random sampling. Technique of collecting data using instrument: (1) questionnaire of self efficacy, (2) questionnaire of emotional intelegence, (3) questionnaire of learning motivation, and (4) test result of mathematics learning. Data were analyzed with descriptive statistics and inferential statistics with path analysis. The result of the research shows that: (1) the student's self efficacy is in the high category, (2) the student's emotional intelegence is in the high category, (3) the student's learning motivation is in the high category, (4) student’s mathematics learning achievement in the medium category, (5) student’s self efficacy directly effect on student’s mathematics learning achievement, (6) student’s emotional intelegence directly effect on student’s mathematics learning achievement, (7) student’s learning motivation directly effect student’s mathematics learning achievement, (8) student’s self efficacy indirectly effect on student’s mathematics learning achievement through variable learning motivation , (9) student’s emotional intelegence indirectly effect on student’s mathematics learning achievement through variable learning motivation.